Norms and Guilt - Anastasia Danilov; Kiryl Khalmetski; Dirk Sliwka (Center for Economic Studies and ifo Institute (CESifo), 2018)
It has been argued that guilt aversion (the aversion to violate others' expectations) and the compliance to descriptive social norms (the aversion to act differently than others in the same situation) are important drivers of human behavior. We show in a formal model that both motives are empirically indistinguishable when only one benchmark (another person's expectation or a norm) is revealed as each of these benchmarks signals information on the other one. To address this problem, we experimentally study how individuals react when both benchmarks are revealed simultaneously. We find that both types of information affect transfers in the dictator game. At the same time, the effect of the recipient's expectation is non-monotonic as dictators use the disclosed expectation in a self-serving way to decrease transfers.
Keywords: C91; D83; D84; 330; guilt aversion; social norms; conformity; dictator game